Den icke-monetära nyttans betydelse för prisbildningen på skogsfastigheter : en intervjuundersökning - Paulsson, Jonas (SLU/Dept. of Forest Products, 2002)
The market value of forest properties can be assumed to consist of two components, a monetary factor and a non-monetary factor. The objective of this examination paper is to study the impact of non-monetary factors on the values of forest properties in Sweden. This study is based on a population of buyers of forest properties in the southern of Sweden. The results are based on interviews with 54 buyers. Of the purchases were 37 % new purchases. i.e. buyers who not before this purchase were owner of a forest property, and 63 % were purchase of addition. The results show that the most important reason of purchase in 25 % of the cases was of monetary nature and in 15 % of the cases of non-monetary nature. In 55 % of the cases the motive for purchase was a combination of monetary and non-monetary reasons. The most important non-monetary part value was the value of the ownership (right of control and pride of ownership). The second and the third most important non-monetary part values were the value of recreation and the value of nature (value of beauty) The impact of the non-monetary factor, in quantitative terms, was as part of the market value on an average 0,26. The value for the new purchases was 0,4 and for the purchases of addition 0,17. In the study has some variables been tested whether they have any effect on the non-monetary factor or not. Only the frequency of visits to the forest property has significant effect on the non-monetary factor. This study has shown that non-monetary utility components are an important factor for the price making of forest properties.